Fusarium spp. an emerging fungal threat to leatherback (Dermochelys coriacea) eggs and neonates - Kuschke, Samantha G.; Wyneken, Jeanette; Cray, Carolyn; Turla, Emily; Kinsella, Megan; Miller, Debra L. (Frontiers in Marine Science, 2023)
Fungal diseases are a rising health problem globally, in humans, nonhuman animals, and plants. Emerging fungal diseases have been associated with mass mortality events. A recent example of fungal disease pathogenicity is sea turtle egg fusariosis (STEF). The pathogenicity of STEF has been linked to fungi within the Fusarium solani species complex (FSSC). This complex is composed of over 45 phylogenetically identifiable species commonly found in the environment. Species within the FSSC lineage have been isolated from the nests of multiple sea turtle species and are linked to decreased hatching success in all 7 of the extant sea turtle species. Fungi within this lineage are also known to cause cutaneous and subcutaneous infections in immunocompromised humans and marine animals. Thus, these fungi are not only a threat to sea turtles but also to other animals, including humans using the waters and beaches inhabited by Fusarium spp. The presence of Fusarium spp. has not been investigated on southeastern Florida beaches which are fundamentally important for at least three sea turtle species that nest there in large numbers. We performed a retrospective assessment of necropsy reports from dead captive leatherback neonates and it revealed that the diagnosis of mycotic dermatitis on histopathology has significantly increased since 2010. An assessment of gross skin lesions associated with mycotic dermatitis in dead captive and live captive leatherback neonates also revealed a similar increase. Additionally, fungal culture results from live captive neonates and dead-in-nest hatchlings and eggs suggest that Fusarium spp. are likely present in leatherback sea turtle nests in Boca Raton and Juno Beach, Florida. Furthermore, based on the occurrence of mycotic dermatitis in dead captive and live captive leatherback neonates it is likely that the presence of Fusarium spp. in the nest is affecting leatherback neonates even after emergence.